2019
DOI: 10.1101/786244
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High-speed quantitative optical imaging of absolute metabolism in the rat cortex

Abstract: Quantitative measures of blood flow and metabolism are essential for improved assessment of brain health and response to ischemic injury. In this report, we demonstrate a multimodal technique for measuring the cerebral metabolic rate of oxygen (CMRO 2 ) in the rodent brain on an absolute scale (M O 2 / min). We use laser speckle imaging (LSI) at 809 nm and spatial frequency domain imaging (SFDI) at 655 nm, 730 nm, and 850 nm to obtain spatiotemporal maps of cerebral blood flow (CBF), tissue absorption ( a ),… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Furthermore, we show that the flow-metabolism ratio (CBF/CMRO 2 ) in the brain at ultra-early time points (1-2 min after ROSC) may be diagnostic of CA severity (duration) and predict bursting, and this metric appears robust across different ischemia durations [190]. Additionally, we recently demonstrated that combining CBF and tissue oxygenation data shows promise for continuously measuring CMRO 2 on an absolute scale (e.g., μM O 2 /min), which has traditionally been more challenging to measure but potentially very important [191]. Absolute CMRO 2 measurement enables direct quantitative comparison between cerebral metabolism of multiple subjects or a single subject on multiple days, without the need for baseline measurements or perturbations such as hypercapnia.…”
Section: Emerging Tools: Diffuse Optical Spectroscopy and Imaging And Spreading Depolarizationmentioning
confidence: 98%
“…Furthermore, we show that the flow-metabolism ratio (CBF/CMRO 2 ) in the brain at ultra-early time points (1-2 min after ROSC) may be diagnostic of CA severity (duration) and predict bursting, and this metric appears robust across different ischemia durations [190]. Additionally, we recently demonstrated that combining CBF and tissue oxygenation data shows promise for continuously measuring CMRO 2 on an absolute scale (e.g., μM O 2 /min), which has traditionally been more challenging to measure but potentially very important [191]. Absolute CMRO 2 measurement enables direct quantitative comparison between cerebral metabolism of multiple subjects or a single subject on multiple days, without the need for baseline measurements or perturbations such as hypercapnia.…”
Section: Emerging Tools: Diffuse Optical Spectroscopy and Imaging And Spreading Depolarizationmentioning
confidence: 98%
“…from the vessels by the tissue, and HbO 2 i, j a is the molar concentration in the arterioles. According to previous studies, (OEF i, j )( HbO 2 i, j a ) is equivalent to the deoxygenated hemoglobin extracted by the tissue, as follows (Ghijsen et al, 2018;Wilson et al, 2019):…”
Section: Calculation Of Oxygen Consumptionmentioning
confidence: 99%
“…However, the reconstructed images of DOT are negatively impacted from poor spatial resolution owing to the diffuse nature of light in biological tissues (Dehghani et al, 2009). To solve spatial resolution, the LSCI technique with high spatial and temporal resolution (Takuwa et al, 2014;Chong et al, 2015;Ghijsen et al, 2018;Wilson et al, 2019) was adopted in combination with the OISI technique. Jones et al first implemented a dual camera and dual light source LSCI and OISI system using a dichroic beam splitter (Jones et al, 2008).…”
Section: Lsci and Oisi Analysis For Pathological And Tissue Metabolism Studies In Ischemic Stroke After Auda Treatmentmentioning
confidence: 99%